2016
DOI: 10.1371/journal.pone.0162712
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Hidden Bat Diversity of a Neotropical Montane Forest

Abstract: Mountain environments, characterized by high levels of endemism, are at risk of experiencing significant biodiversity loss due to current trends in global warming. While many acknowledge their importance and vulnerability, these ecosystems still remain poorly studied, particularly for taxa that are difficult to sample such as bats. Aiming to estimate the amount of cryptic diversity among bats of a Neotropical montane cloud forest in Talamanca Range—south-east Central America—, we performed a 15-night sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 95 publications
0
16
0
2
Order By: Relevance
“…Hipposideros caffer and Myotis tricolor), suggesting the possibility of high genetic divergence in the Taita Hills when compared to populations elsewhere. Although the results presented here are based on only one specimen per species, this genetic divergence could be caused by isolation between the hilltops and lowlands, driven by the extreme elevational gradients in the Taita Hills (Chaverri et al 2016). This "topographic isolation" often leads to high levels of endemism, a pattern described for several montane landscapes (Chaverri et al 2016, Steinbauer et al 2016.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Hipposideros caffer and Myotis tricolor), suggesting the possibility of high genetic divergence in the Taita Hills when compared to populations elsewhere. Although the results presented here are based on only one specimen per species, this genetic divergence could be caused by isolation between the hilltops and lowlands, driven by the extreme elevational gradients in the Taita Hills (Chaverri et al 2016). This "topographic isolation" often leads to high levels of endemism, a pattern described for several montane landscapes (Chaverri et al 2016, Steinbauer et al 2016.…”
Section: Discussionmentioning
confidence: 88%
“…In addition to their role as refuge, the diverse climatic conditions and habitat heterogeneity within these ecosystems promotes the development of diverse species traits (Presley et al 2012, Cisneros et al 2014, Chaverri et al 2016, Peters et al 2016, Badgley et al 2017. This, combined with restricted genetic exchange across elevational gradients, drives evolutionary divergence and endemism (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, no hay que olvidar que los murciélagos cumplen roles positivos en el ecosistema, al ser polinizadores, dispersores de semillas, controladores biológicos de plagas y bioindicadores de impactos antrópicos (Chaverri et al, 2016;Ferreira et al, 2017;Oliveira et al, 2017). También son excelentes objetos de investigaciones en envejecimiento saludable, prevención del cáncer, defensa de enfermedades, ingeniería biomédica, funcionamiento ecosistémico y evolución adaptativa (Zhao, 2020).…”
Section: Discusión Y Conclusionesunclassified
“…Myotis keaysi as envisioned by Stadelmann et al 2007 andRuedi et al 2013 was identified as a monophyletic clade with considerable geographic structure and at least three different lineages (Larsen et al 2012a;Chaverri et al 2016), which were named as follows: M. keaysi (Yucatán Peninsula, México), M. cf. keaysi 2 (México, El Salvador, Guatemala), and an unnamed clade from the mountain tops of Cordillera Oriental from Ecuador and Panamá (Clare et al 2011;Larsen et al 2012b) that was later suggested to be M. keaysi (Costa Rica) in Chaverri et al (2016).…”
Section: Introductionmentioning
confidence: 99%